Near-threshold processor design techniques for power-constrained computing devices - Zhou, Jun (2019)
Ultra-low power digital processors are needed in power-constrained computing devices for IoT, intelligent sensing and wearable computing applications. While near-threshold design is promising to achieve ultra-low power consumption, there are several challenges for this technology to be applied to the design of digital processors, including the functionality issue, performance degradation and variability issue. This paper reviews the existing near-threshold processor design techniques including circuit and architecture level solutions and discuss how the aforementioned issues can be addressed.